2017
DOI: 10.1371/journal.pone.0185198
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of treatment with non-curative or palliative intent for hepatocellular carcinoma in the real-world setting

Abstract: Hepatocellular carcinoma (HCC) presentation is heterogeneous necessitating a variety of therapeutic interventions with varying efficacies and associated prognoses. Poor prognostic patients often undergo non-curative palliative interventions including transarterial chemoembolization (TACE), sorafenib, chemotherapy, or purely supportive care. The decision to pursue one of many palliative interventions for HCC is complex and an economic evaluation comparing these interventions has not been done. This study evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…89 A similar study by the same group comparing noncurative palliative interventions, including TACE, sorafenib, chemotherapy, or purely supportive care, reported that TACE with or without sorafenib was the most cost-effective palliative treatment at $6665 per QALY. 90 A Monte-Carlo model study from Taiwan comparing sorafenib with HIGRT indicated that HIGRT was the most cost-effective treatment and was aligned with the current accepted QALY threshold in Taiwan (approximately $67K [in US dollars] per QALY). 91 A US-based Markov model study comparing RFA with HIGRT treatment sequencing (assuming locally progressive disease after RFA or HIGRT requiring second treatment and a threshold of $100K per QALY) demonstrated that RFA was the most cost-effective initial treatment and that HIGRT was the preferred salvage treatment for locally recurrent disease.…”
Section: Cost Analysismentioning
confidence: 92%
“…89 A similar study by the same group comparing noncurative palliative interventions, including TACE, sorafenib, chemotherapy, or purely supportive care, reported that TACE with or without sorafenib was the most cost-effective palliative treatment at $6665 per QALY. 90 A Monte-Carlo model study from Taiwan comparing sorafenib with HIGRT indicated that HIGRT was the most cost-effective treatment and was aligned with the current accepted QALY threshold in Taiwan (approximately $67K [in US dollars] per QALY). 91 A US-based Markov model study comparing RFA with HIGRT treatment sequencing (assuming locally progressive disease after RFA or HIGRT requiring second treatment and a threshold of $100K per QALY) demonstrated that RFA was the most cost-effective initial treatment and that HIGRT was the preferred salvage treatment for locally recurrent disease.…”
Section: Cost Analysismentioning
confidence: 92%
“…Based on Markov modelling, it has been suggested that RFA is more cost-effective than SBRT as the initial management of unresectable HCC, however, for recurrent disease, SBRT was favored over repeat RFA [74] . Another study demonstrated that the addition of TACE to sorafenib or non-sorafenib chemotherapy is more cost effective than systemic therapy alone [75] . As the financial burden rises, some resources may become limiting, and physicians and their patients will need to have open discussions regarding the wise utilization of available options that meet their personal goals.…”
Section: Selection Of Treatment Modalitymentioning
confidence: 99%
“…Currently, the diagnosis of HCC is mainly based on the detection of serum alphafetoprotein (AFP), B-ultrasound, and computed tomography imaging. However, the misdiagnosis and missed diagnosis rates are very high [6][7][8]. Owing to the insidious onset, poor tumor biological behavior, and rapid progress of HCC, most patients reach advanced stage of the disease and miss the opportunity for radical treatment.…”
Section: Introductionmentioning
confidence: 99%